1997
DOI: 10.1007/bf02348475
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Planting Density for Japanese Oak (Quercus mongolica var. grosseserrata) Based on Spacing Experiment with Systematic Design

Abstract: A spacing experiment for Japanese oak (Quercus mongolica var. grosseserrata) with Nelder's design have been studied at the Kyushu University Forest in Hokkaido, since 1975. The oak seedlings were planted according to systematic spacings which were 20 levels varying gradually from 40,816 to 1,086 seedlings per hectare with concentric circular arcs (22 in number) and spokes (41 in number). In 1992 when the planted oak seedlings were 18-year-old, DBH, crown diameter, total height and clear length of the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
(2 reference statements)
0
9
0
1
Order By: Relevance
“…A review of literature shows that growth behaviour is affected by several external factors (Ryan and Yoder 1997;Yin et al, 2004). For example, Nelder experimental plot (Nelder, 1962) suggests that, density affects growth behaviour (Imada, 1997). Such external factors can be integrated as explanatory variables.…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature shows that growth behaviour is affected by several external factors (Ryan and Yoder 1997;Yin et al, 2004). For example, Nelder experimental plot (Nelder, 1962) suggests that, density affects growth behaviour (Imada, 1997). Such external factors can be integrated as explanatory variables.…”
Section: Introductionmentioning
confidence: 99%
“…Esses delineamentos, inicialmente utilizados na área agrícola, foram usados na área florestal para estudos preliminares (FREEMAN, 1964;BLEASDALE, 1966;PANETSOS, 1980;HUXLEY, 1985;IMADA et al, 1997). Além de permitir avaliar maior número de espaçamentos possíveis, os delineamentos sistemáticos também se destacam pela sua compacidade, necessitando de pequenas áreas experimentais que facilitam o manejo e abrangência.…”
Section: Introductionunclassified
“…grosseserrata plantations (Imada et al, 1987 Sano and Manabe (1989) summarized the first and second set of measurement data. They found that even before canopy closure, individuals of the light tolerant Larix kaempferi plots were already competing with each other and there were possible density effects.…”
Section: Introductionmentioning
confidence: 99%